Insiders or Outsiders Within? Immigrants in the Finnish Labor Market - Annika Forsander (Finnish Yearbook of Population Research, 2003)
This article focuses on the position of immigrants on the Finnish labor marketin the context of recent migration history and the disintegration of the traditional paid-work society. Finland is a so-called late immigration country, where a positive trend in migratory movements did not begin until the beginning of the l 990s and where the labor migration phase after WWII was experienced not as an immigration country but as ane of emigration. One outcome of this is that immigrants are treated in society as a social burden rather than a labor resource. Results of an empirical study concerning immigrants in the Finnish labor market indicate that more than a half of immigrants who have been residing in Finland for several years have an unstable labor market career, and almost one-third of them are in the margins of the Finnish labor market. It seems that in Finland, as in the labor markets in many other postindustrial societies, immigrants are acting as a buffer against upswings and downswings in the economy.